COMPARING THE INFLUENCE OF RELAXATION TRAINING AND CONSUMPTION OF VALERIAN ON INSOMNIA OF MENOPAUSEWOMEN: A RANDOMIZED CLINICAL TRIAL - Jokar, Azam; Kargosha, Atefe; Akarzadeh, Marzieh; Asadi, Nasrin; Setoudeh, Zahra (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Sleep disturbance is one of the symptoms of menopause, which occurs due to a decrease in sex hormones and dramatically affects the quality of life. This study was designed to compare the effects of relaxation and Valerian on insomnia of menopause women. Methods: The study was a randomized clinical trial in 129 menopausal women with insomnia that were randomly allocated to three groups valerian, relaxation and control. After 1 month information obtained by demographic questionnaire and sleep quality Petersburg, then data analyzed in the software SPSS20 at a significance level of 0.05. Results: The results showed there was significant difference in the level of education , age of marriage(p<0.05 ).Comparing average scores before and after treatment of sleep disorders were determined in valerian and relaxation group was significant difference (p <0.001) and in the control group no correlation was found (p >0.05). Conclusion: This study showed that the herb valerian and relaxation techniques effective for menopausal insomnia and helps to increase the quality of their sleep.